If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(x + 3) = 6 + -1(7x + 2) Reorder the terms: 3x(3 + x) = 6 + -1(7x + 2) (3 * 3x + x * 3x) = 6 + -1(7x + 2) (9x + 3x2) = 6 + -1(7x + 2) Reorder the terms: 9x + 3x2 = 6 + -1(2 + 7x) 9x + 3x2 = 6 + (2 * -1 + 7x * -1) 9x + 3x2 = 6 + (-2 + -7x) Combine like terms: 6 + -2 = 4 9x + 3x2 = 4 + -7x Solving 9x + 3x2 = 4 + -7x Solving for variable 'x'. Reorder the terms: -4 + 9x + 7x + 3x2 = 4 + -7x + -4 + 7x Combine like terms: 9x + 7x = 16x -4 + 16x + 3x2 = 4 + -7x + -4 + 7x Reorder the terms: -4 + 16x + 3x2 = 4 + -4 + -7x + 7x Combine like terms: 4 + -4 = 0 -4 + 16x + 3x2 = 0 + -7x + 7x -4 + 16x + 3x2 = -7x + 7x Combine like terms: -7x + 7x = 0 -4 + 16x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -1.333333333 + 5.333333333x + x2 = 0 Move the constant term to the right: Add '1.333333333' to each side of the equation. -1.333333333 + 5.333333333x + 1.333333333 + x2 = 0 + 1.333333333 Reorder the terms: -1.333333333 + 1.333333333 + 5.333333333x + x2 = 0 + 1.333333333 Combine like terms: -1.333333333 + 1.333333333 = 0.000000000 0.000000000 + 5.333333333x + x2 = 0 + 1.333333333 5.333333333x + x2 = 0 + 1.333333333 Combine like terms: 0 + 1.333333333 = 1.333333333 5.333333333x + x2 = 1.333333333 The x term is 5.333333333x. Take half its coefficient (2.666666667). Square it (7.111111113) and add it to both sides. Add '7.111111113' to each side of the equation. 5.333333333x + 7.111111113 + x2 = 1.333333333 + 7.111111113 Reorder the terms: 7.111111113 + 5.333333333x + x2 = 1.333333333 + 7.111111113 Combine like terms: 1.333333333 + 7.111111113 = 8.444444446 7.111111113 + 5.333333333x + x2 = 8.444444446 Factor a perfect square on the left side: (x + 2.666666667)(x + 2.666666667) = 8.444444446 Calculate the square root of the right side: 2.905932629 Break this problem into two subproblems by setting (x + 2.666666667) equal to 2.905932629 and -2.905932629.Subproblem 1
x + 2.666666667 = 2.905932629 Simplifying x + 2.666666667 = 2.905932629 Reorder the terms: 2.666666667 + x = 2.905932629 Solving 2.666666667 + x = 2.905932629 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.666666667' to each side of the equation. 2.666666667 + -2.666666667 + x = 2.905932629 + -2.666666667 Combine like terms: 2.666666667 + -2.666666667 = 0.000000000 0.000000000 + x = 2.905932629 + -2.666666667 x = 2.905932629 + -2.666666667 Combine like terms: 2.905932629 + -2.666666667 = 0.239265962 x = 0.239265962 Simplifying x = 0.239265962Subproblem 2
x + 2.666666667 = -2.905932629 Simplifying x + 2.666666667 = -2.905932629 Reorder the terms: 2.666666667 + x = -2.905932629 Solving 2.666666667 + x = -2.905932629 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.666666667' to each side of the equation. 2.666666667 + -2.666666667 + x = -2.905932629 + -2.666666667 Combine like terms: 2.666666667 + -2.666666667 = 0.000000000 0.000000000 + x = -2.905932629 + -2.666666667 x = -2.905932629 + -2.666666667 Combine like terms: -2.905932629 + -2.666666667 = -5.572599296 x = -5.572599296 Simplifying x = -5.572599296Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.239265962, -5.572599296}
| 4x-1=-2(x-1) | | Y=2x^2+8x-30 | | 2x+1+x+1=18 | | 2-2(4+9a)= | | -6+9(x-1)=16x+2-7x | | 9+2i=0 | | 7(x+4)-3=29-2x-4+9x | | -28=x-3.7 | | 200/x=3x | | 1/4-x=3/x | | (d^3+d^2-4d)y=0 | | 4(b+3)=9 | | 12x+11=156 | | 28y+4x=4 | | -3p/2;0 | | x^2=16y-32 | | 25=18-2y | | -2(5x-9)+7=-10X+25 | | -26=9+5x | | 7x(2)=63 | | (3/5)2 | | 0.25x=(9/365)x | | x^4-12x^3+36x^2-20x+3=0 | | x+(x*.12)=765 | | I-(1+7x)-6(-7-x)=36 | | 15/20=3/x | | 8.3w-w-8.9=1.5 | | -6x-6=10 | | 19/21-2/3 | | 6y+9=2thirdsx | | -6x+3=10 | | X^2-45x+506=0 |